PERAN MU’ALLIM DAN MU’ALLIMAH MEMBINA AKHLAK MAHASANTRI MA’HAD AL-JAMI’AH UIN RADEN INTAN LAMPUNG - Andini, Resti; Patimah, Siti; Bedi, Fisman; Mas Ayu, Sovia; Junaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Ma’had Al-Jami’ah as an educational institution plays an important role in fostering the morals of students. Mu’allim and Mu’allimah have an obligation to foster students to have good morals at Ma’had Al-Jami’ah UIN Raden Intan Lampung. The purpose of the study was to find the Mu’allim and Mu’allimah program in fostering the morals of students. The study used a qualitative research approach with a phenomenological design. The study focused on Mu’allim and Mu’allimah and students to determine the role of Kyai in fostering the morals of students at Ma’had Al-Jami’ah UIN Raden Intan Lampung. Data collection steps through observation, interviews, and documentation. Analysis with data reduction, data display, and data verification. Research results: The results of moral development at Ma’had Al-Jami’ah UIN Raden Intan Lampung have shown good changes, especially the morals of students that can be formed even though not all students can show this. There are students who still have bad behavior, namely those who have a background of free association before entering the Islamic Boarding School, as a result, some students find it difficult to obey the rules/regulations made by the Ma'had Aljami'ah Uin Raden Intan Lampung.